A coisa julgada coletiva - Almeida, Cezar Augusto Pinheiro de (2014)
This work firstly makes revisiting the Institute of res iudicata under the classic civil procedure bias - concept, legal, limits, assumptions of incidence, and sums up the causes and means of removal - to subsequently introduce it forward to the new branch of law, in which oversee metaindividual interests. That focus on further brief clarification of collective suits, considering its origin, the relevant aspects and comparisons of the traditional civil procedure, including the study of parties and their legitimation. In conclusion, the collective res judicata, erected the protagonist, is analyzed according to the legal provisions, the doctrinal and jurisprudential investigations that address and problematize. Moreover, through theoretical and empirical analysis, were sought on the law, doctrine and jurisprudence homeland, the best results concerning the most suitable for the purpose of metaindividual guardianships results, allying the premises of Collective Law, Civil Procedure Law of the traditional and judged collective thing, and a deductive exposition on this last technique